Potential of animal, crop and agri-food wastes for the production of fly larvae - GANDA, Haffizou; ZANNOU, BOUKARI ELISABETH TOHOUÉDÉ; KENIS, Marc; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; MENSAH, GUY APOLLINAIRE (My University, 2019)
Fly larvae, especially those of the house fly (Musca domestica) and the black soldier fly (Hermetia illucens), are increasingly being considered worldwide for animal feed. A simple way to produce fly larvae is to expose suitable substrates to attract adult flies that will lay their eggs in the substrates from which the larvae will then be extracted. This study aims to evaluate the potential of animal substrates and agri-food wastes for the production of larvae and to identify the species of flies that develop in the substrates. Experiments were conducted in Benin where twenty-six substrates were left in free (i.e. uncovered) oviposition for 10 hours and maggots from the eggs laid were collected after four days. The fresh substrates were then added to the residual substrates and left in the open air for an additional 10 hours for another production cycle. A total of three production cycles were followed. In the first cycle, nearly 100% of the species were houseflies, but black soldier flies appeared in the following cycles. The result showed that plant and agro-food substrates produced more larvae than hog manure. The highest yield in the first production cycle was obtained with the mixture of soybean bran and corn pericarp. Corn bran, pig manure and chicken manure also showed potential for maggot production. Other substrates such as cow and sheep dung produce virtually no maggots when used alone, but the amount of larvae increases considerably when attractants such as chicken offal are added, or when mixed with pig manure and chicken droppings. Maggot production decreases with production cycles for most substrates, except for mixtures based on spent grains and pineapple seeds, which produced a large quantity of larvae in the second harvest. Maggot activity resulted in a rise in temperature and a reduction in substrate biomass. This study showed that several substrates, in particular soybean bran, corn bran, pork manure and chicken manure, have potential for maggot production.
Keywords: Musca domestica; Hemertia illucens; maggot yield; substrate reduction; Benin